Effects of Huangqi Gancao Decoction on intestinal immunity and microbiota in immunocompromised mice models - Zhou, Hai; Yan, Jianpeng; Zhou, Ke; Ji, Peng; Wei, Yanming; Hua, Yongli (Frontiers in Pharmacology, 2024)
The classical medicinal formula Huangqi Gancao Decoction (HQGCD), originating from the medical book" Yi Lin Gai Cuo". Up to now, the studies focusing on the immunoenhancement effects of HQGCD are few, and the actionpathway is not yet clear.In this study, SPF male KM mice were utilized as a model for immunosuppression.Comprehensive observations were made regarding the general behavior and condition of the mice, in addition to monitoring fluctuations in body weight and food intake. The blood routine index was measured, and morphological changes in the ileum and colon tissues were examined. The level of secretory immunoglobulin A (sIgA), superoxide dismutase (SOD), and malondialdehyde (MDA) in ileum and colon tissues were quantified. Additionally, the bone marrow total DNA index was assessed. Flow cytometry analyzed the proportions of CD3⁺, CD4⁺, CD8⁺, and CD4 + CD8 + doublepositive (DP) T lymphocytes in small intestinal intraepithelial lymphocytes (IELs). Lastly, the composition and diversity of the cecal microbiota were evaluated using 16S rDNA sequencing technology.Results: After HQGCD intervention, there were no significant changes in the mice's feed intake and body weight. However, the tissue structures of the ileum and colon showed recovery. In the blood routine index, there was an increase in the total white blood cell count, lymphocyte count, red blood cell count, hematocrit, and hemoglobin content. Additionally, the bone marrow total DNA index was elevated. Level of SOD and sIgA in ileum and colon tissues increased, while the level of MDA decreased. The proportions of CD3⁺ and CD4⁺ T lymphocytes within IELs increased, along with an increase in DP T lymphocytes in IELs (DP IELs), whereas the proportion of CD8⁺ T lymphocytes decreased. The cecal microbiota underwent changes, with an increase in the variety and number of beneficial microbiota. Conclusion: HQGCD could restore the intestinal immune function of immunocompromised mice, and had a certain positive effect on cecal microbiota.